PENGEMBANGAN BUDIDAYA IKAN GURAME SEBAGAI WAHANA LAPANGAN KERJA BARU DI DESA MLARAS SUMOBITO JOMBANG - Mahfudiyanto Mahfudiyanto; Lik Anah; Lilis Sugi Rahayu; M. Adi Trisna Wahyudi (Universitas Islam Malang, 2023)
The management of fisheries economic activities is an integral part of agricultural businesses and cannot be separated. One of the obstacles faced is the lack of management in gourami fish farming, so that many farmers cannot develop their business. The purpose of this community service programme (PKM) is to provide training to village youth so that the Mlaras community can be more independent. Participants in this PKM activity are youth from Mlaras village in the Mitra area who have the drive and ambition to improve their situation and create new economic ventures. The challenges faced are the lack of knowledge and skills among the youth in Mlaras village regarding the management of carp farming, especially in tarpaulin ponds, and regarding aquaculture business planning, in addition to good aquaculture technology, such as feed distribution management, has not been widely adopted by the community. This activity uses a direct approach by involving members of the fish farming community in the Partner area. Activities are carried out through theoretical counselling, hands-on practice, and mentoring in the field to provide access to the community to real knowledge and experience. The positive impact resulting from this PKM activity is that participants gain knowledge and skills related to fish breeding management.